2012 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2012
DOI: 10.1109/icassp.2012.6288669
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty principles for signals defined on graphs: Bounds and characterizations

Abstract: The classical uncertainty principle provides a fundamental tradeoff in the localization of a signal in the time and frequency domains. In this paper we describe a similar tradeoff for signals defined on graphs. We describe the notions of "spread" in the graph and spectral domains, using the eigenvectors of the graph Laplacian as a surrogate Fourier basis. We then describe how to find signals that, among all signals with the same spectral spread, have the smallest graph spread about a given vertex. For every po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 7 publications
1
30
0
Order By: Relevance
“…Varying the parameter allows one to "trace" and obtain the entire curve . A rigorous and complete proof of Theorem 1 is provided in this paper, extending the rough argument given in [25]. Based on the convexity of , we show in Section III-C that the sandwich algorithm [26] can be used to efficiently produce a piecewise linear approximation for the uncertainty curve that differs from the true curve by at most (under a suitable error metric) and requires solving typically sparse eigenvalue problems.…”
Section: B Contributions and Paper Organizationmentioning
confidence: 70%
See 2 more Smart Citations
“…Varying the parameter allows one to "trace" and obtain the entire curve . A rigorous and complete proof of Theorem 1 is provided in this paper, extending the rough argument given in [25]. Based on the convexity of , we show in Section III-C that the sandwich algorithm [26] can be used to efficiently produce a piecewise linear approximation for the uncertainty curve that differs from the true curve by at most (under a suitable error metric) and requires solving typically sparse eigenvalue problems.…”
Section: B Contributions and Paper Organizationmentioning
confidence: 70%
“…After justifying the use of the Laplacian eigenvectors as a Fourier basis on graphs, we define in Section II-C the graph spread about a vertex , and the spectral spread, , of a signal defined on a graph. These two quantities, which we first introduced in some preliminary work [24], [25], are defined in analogy to the standard time and frequency spreads, respectively.…”
Section: B Contributions and Paper Organizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples include uncertainty principle on graphs [1], on spheres [14], and on Riemannian manifolds [8]. Studies on the periodic frequency spread can be found in [4] and [35].…”
Section: Related Workmentioning
confidence: 99%
“…Examples include uncertainty principle on graphs [10] and on spheres [11]. Initial studies on the periodic frequency spread were undertaken by [3] and [12].…”
Section: Related Workmentioning
confidence: 99%